2016
DOI: 10.1002/adfm.201603491
|View full text |Cite
|
Sign up to set email alerts
|

Role of Molecular Sieves in the CVD Synthesis of Large‐Area 2D MoTe 2

Abstract: The synthesis of high‐quality 2D MoTe2 with a desired phase on SiO2/Si substrate is crucial to its diverse applications. A side reaction of Te with the substrate Si leading to SiTe and Si2Te3 tends to happen during growth, resulting in the failure to obtain MoTe2. It has been found that molecular sieves can adsorb the silicon telluride byproducts and eliminate the influence of the side reaction during the chemical vapor deposition synthesis of MoTe2. With the help of molecular sieves, few‐layer 1T′ MoTe2 can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 34 publications
4
72
0
Order By: Relevance
“…The optical and electrical properties of 2H MoTe 2 films prepared using a mechanical exfoliated method have been widely investigated . Most recently, owing to the growing interest in large‐scale synthesis of MoTe 2 , several groups have reported the preparation of 1T′ and 1T phase films via phase‐engineered techniques using laser patterning, strain on 2H phase films, and chemical vapor deposition (CVD) . Tunable growth conditions, such as temperature and carrier gas flow rate, make CVD a suitable technique for phase engineering of MoTe 2 films .…”
mentioning
confidence: 99%
“…The optical and electrical properties of 2H MoTe 2 films prepared using a mechanical exfoliated method have been widely investigated . Most recently, owing to the growing interest in large‐scale synthesis of MoTe 2 , several groups have reported the preparation of 1T′ and 1T phase films via phase‐engineered techniques using laser patterning, strain on 2H phase films, and chemical vapor deposition (CVD) . Tunable growth conditions, such as temperature and carrier gas flow rate, make CVD a suitable technique for phase engineering of MoTe 2 films .…”
mentioning
confidence: 99%
“…The inset in the lower-right corner displays a fit to the resistivity data in between 5 and 35 K to a combination of electron-phonon scattering and Fermi-liquid mechanisms. The form of the fitted equation is ρ xx = ρ 0 + cT 2 + gT 5 where ρ 0 is the residual resistivity due to impurity scattering; c and g are fitting parameters to Fermi-liquid (~T 2 ) and electron-phonon scattering (~T 5 ) mechanisms at low temperatures [13,23]. From the best fit, we found ρ 0 = 210 µΩ cm and other fitting parameters are c = 711 × 10 -4 µΩ cm K -2 , and g = 212 × 10 -10 µΩ cm K -5 .…”
Section: B Results and Discussionmentioning
confidence: 99%
“…For example, by inverting the substrate coated with MoO x over the tellurium powder and molecular sieves, Kong and co‐workers synthesized the MoTe 2 thin film successfully as shown in Figure c,d . They found that molecular sieves could adsorb the by‐products (Si 2 Te 3 ) to promote the formation of target products . Moreover, the phases of MoTe 2 film were tunable under different tellurization velocity and the cooling down temperature …”
Section: Preparationmentioning
confidence: 97%
“…Besides, CVD is also a conventional strategy for thin‐film synthesis . For example, by inverting the substrate coated with MoO x over the tellurium powder and molecular sieves, Kong and co‐workers synthesized the MoTe 2 thin film successfully as shown in Figure c,d . They found that molecular sieves could adsorb the by‐products (Si 2 Te 3 ) to promote the formation of target products .…”
Section: Preparationmentioning
confidence: 99%
See 1 more Smart Citation